Can we teach children to be good? : basic issues in moral, personal, and social education - Straughan, Roger (London : Routledge, 2012)
The apparently straightforward question 'Can we teach children to be good?' cannot be properly understood without a great deal of careful thinking about the philosophical issues involved. Teachers and parents often assume that what the question means and how it should be answered are self-evidently matters of plain 'commonsense', but the dangers of such assumptions are laid bare by the probing approach of this book. After reflecting on the terms 'goodness' and 'teaching' it proceeds to describe and critically examine a number of attempts to define the nature of morality in terms of its form or its content, thereby teasing out the many conflicting views of moral education which follow from these theories. No one account of morality or 'moral education' is found to be wholly satisfactory and a synthesis is offered in the final chapter, which suggests a variety of practical teaching strategies.
Includes bibliographical references and index.
Keywords: Education -- Philosophy; Education -- Aims and objectives; Moral education